PENERAPAN METODE-METODE LATIHAN UNTUK MENINGKATKAN KEMAMPUAN GURU DALAM MENGANALISIS STANDAR KOMPETENSI DAN KOMPETENSI DASAR - Asperi Asperi (JURNAL PENDIDIKAN ROKANIA, 2017)
Based on temporary observation of several teachers, the following symptoms were found: 1) Lack of teacher ability to analyze CompetencyStandards and basic competencies 2) lack of teacher ability in making correct implementation plan and 3) lack of teacher ability in developing learning model which corresponds to the character of the learner. The circumstances mentioned above, is a sourceof inspiration for writers to do a scientific related to the ability of teachers in Analyzing SK and KD. The type of research is the study of school action (PTS)which aims to know the success of the Application of Exercise Methods To Improve Teacher Ability in Analyzing SK and KD at SDN 007 Pendalian IV Koto. The population in this study is all teachers amounted to 14. From the description of data processing and discussion it can be concluded that the ability of Teachers in Analyzing SK and KD obtained in the first cycle of 65% with good enough category and in the second cycle increased to 75% with good category.